GAMBARAN TINGKAT PENGETAHUAN SISWA TENTANG PENCABUTAN GIGI DI SMP NEGERI 40 MAKASSAR - Zulkarnain, Zulkarnain; Maknung, Afdal; Puspita, Nadia Emi; Pariati, Pariati; Alfah, Siti; Rahmadani, Nanang (Jurnal Ilmiah Amanah Akademika, 2022)
Tooth extraction is one of the best solutions to prevent abnormalities in the oral cavity. Tooth extraction sometimes experiences obstacles, generally the obstacles that occur in dental health service efforts are due to a lack of knowledge of the tooth extraction community. The aim of this research was to determine the level of students' knowledge about tooth extraction at SMP Negeri 40 Makassar. This research is descriptive in nature with a sample size of 198 students taken using the Slovin formula. The research results showed that students' knowledge about tooth extraction at SMP Negeri 40 Makassar was said to be lacking because students who answered correctly from the scoring results only got a score of 822 or 46.1%, while students who answered incorrectly were 53.9%. The percentage of students' knowledge about indications for tooth extraction is 50%. The percentage of students' knowledge about indications for tooth extraction is 47.2%. The percentage of students' knowledge about the benefits of tooth extraction was 38.9%. The percentage of students' knowledge about the side effects of teeth that are indicated but not removed is 46.6%.